Chemical Synthesis and Substrate Temperature Effect on Morphology of 2D Vanadium Disulfide. Issue 3 (27th January 2021) - Hossain, Mongur; Qin, Biao; Sen, Sapan Kumar
Abstract: 2D metallic transition metal dichalcogenides exhibit plenty of intriguing physical properties such as magnetism, charge density wave, and superconductivity resulting in worldwide attention from condensed‐matter physicists over the last few decades. Herein, the chemical synthesis and substrate temperature effect on the morphology of 2D vanadium disulfide (VS2 ) are reported. The synthesis is done by atmospheric pressure chemical vapor deposition using vanadium chloride (VCl3 ) precursor on SiO2 /Si, fluorphlogopite mica, and hexagonal boron nitride ( h ‐BN) substrates. The effect of substrate temperatures on the morphology of 2D VS2 nanosheets growth is investigated by optical microscopy, scanning electron microscopy, and atomic force microscopy. Large area VS2 films are attained when the substrate temperature is 650 °C whereas VS2 single crystals are obtained at 550 °C. Abstract : 2D vanadium disulfide (VS2 ) is synthesized by atmospheric pressure chemical vapor deposition on SiO2 /Si, fluorphlogopite mica, and h ‐BN substrates. Corresponding to dissimilar temperatures, the effect of substrate position on VS2 growth shows large area VS2 films are attained when the substrate temperature is 650 °C whereas VS2 single crystals are obtained at 550 °C.